The Recoil Directionality (ReD) Experiment. Issue 1 (1st November 2022) - Sanfilippo, S; Agnes, P; Albergo, S; Albuquerque, I; Arba, M; Ave, M; Boiano, A; Bonivento, W M; Bottino, B; Bussino, S; Cadeddu, M; Caminata, A; et al.
Abstract : Directional sensitivity to nuclear recoils would provide a smoking gun for a possible discovery of dark matter in the form of WIMPs (Weakly Interacting Massive Particles). A hint of directional dependence of the response of a dual-phase argon Time Projection Chamber (TPC) was found in the SCENE experiment. Given the potential importance of such a capability in the framework of dark matter searches, a new dedicated experiment, ReD (Recoil Directionality), was designed by the Global Argon Dark Matter Collaboration, in order to scrutinize this hint. Prior to the irradiation with a neutron beam, the ReD TPC underwent a long campaign of characterization and optimization: some selected results are presented in this contribution.